Fungal endophthalmitis in a case of granulomatosis with polyangitis - AlQahtani, Ghadah Mohammed S. (Saudi J Ophthalmol, 2018)
A 70-year-old immuno-compromised man, due to multiple comorbidities, particularly granulomatosis with polyangitis (GPA) and its related treatment, presented with generalized weakness, odynophagia and loss of taste sensation. After a complete evaluation, a diagnosis of right frontal lobe brain abscess was made. The patient then developed headache and sudden painful loss of vision in the right eye. Clinical examination revealed anterior chamber cells and flare, vitreous haze and cells, and hemorrhagic chorioretinitis with severe vasculitis in the right eye. Culture from the drained pus of the frontal brain abscess came positive for Aspergillus fumigatus. Incidental echocardiogram showed large vegetation in the mitral valve. Pars plana vitrectomy was done and a specimen was sent for culture that came positive for Aspergillus fumigatus. Although all the necessary medical and surgical interventions were timely carried out in the affected right eye, the patient’s vision worsened due to retinal damage.